Per le riviste di Vecchietti negli anni '30-'40 Raccolta di racconti e scritti dispersi - Dessì, Giuseppe (Moderna/Comparata, 2016)
Retracing Dessí's collaboration in the magazines "L'Orto", "Primato" and "Cronache" directed by Giorgio Vecchietti, among stories, essays and reviews that have remained largely unpublished, means deepening the writer's artistic development by exploring into the creative laboratory of his debut. The 36 texts collected and commented by Francesca Bartolini allow us to analyse the thematic and stylistic approaches that were further developed and deepened in the subsequent production. At the same time they take into account the years of the fascist dictatorship, allowing us to investigate the development of an intellectual conscience engaged in an anti-fascist, rebel movement typical of many writers of that generation. Weaving the critical discourse with the reading of the correspondence, the complex relationship that linked Dessí to the three editorial offices is noted, testifying to the passion of a young artist eager to follow his inclination, but also aware of the difficulty of preserving his freedom and identity in the limitations of the regime.